Hubungan neutrophil-lymphocyte ratio, absolute lymphocyte count, dan platelet lymphocyte ratio terhadap derajat keparahan COVID-19 - Lusia Nasrani (DiscoverSys Inc., 2022)
Introduction: The COVID-19 virus was discovered at the end of 2019 as respiratory infectious disease and has become a pandemic until now, so it is very important to predict the severity of COVID-19. Neutrophil Lymphocyte Ratio (NLR), Absolute Lymphocyte Count (ALC), and Platelet Lymphocyte Ratio (PLR) are easy, inexpensive, and fast methods as screening tools for the severity of COVID-19. The purpose of this study was to determine the relationship between NLR, ALC, and PLR to the severity of COVID-19.Methods: This study is an analytic observational study with a cross-sectional research design—retrieving research data using the total sampling method. The research data are medical records and laboratory examination data from 64 COVID-19 patients at Harapan Keluarga Hospital Cikarang in July–December 2020. The data analysis used was bivariate analysis with chi-square.Results: There were 64 samples in this study, with the majority of samples being male, the average age was 42 years, the most common symptoms were fever (81.3%) and cough (71.9%), the majority of patients had no comorbidities. There was a significant relationship between NLR, ALC and PLR with the severity of COVID-19 (p = 0.007; p = 0.002; p = 0.013). Latar belakang: Virus COVID-19 ditemukan pada akhir tahun 2019 sebagai penyakit infeksi pada pernapasan dan telah menjadi pandemi hingga saat ini, sehingga sangat penting untuk memprediksi derajat keparahan COVID-19. Neutrophyl Lymphocyte Ratio (NLR), Absolute Lymphocyte Count (ALC), dan Platelet Lymphocyte Ratio (PLR) merupakan metode yang mudah, murah, dan cepat sebagai alat skrining pada keparahan COVID-19. Tujuan penelitian ini adalah untuk mengetahui hubungan NLR, ALC, dan PLR terhadap derajat keparahan COVID-19.Metode: Penelitian ini adalah suatu penelitian observasional analitik dengan desain penelitian crosssectional. Pengambilan data penelitian menggunakan metode total sampling. Data penelitian adalah data rekam medis dan pemeriksaan laboratorium dari 64 pasien COVID-19 di RS Harapan Keluarga Cikarang pada periode Juli–Desember 2020. Analisis data yang digunakan adalah analisis bivariat dengan chi-square.Hasil: Terdapat 64 sampel pada penelitian ini dengan mayoritas sampel merupakan laki-laki, rata-rata usia 42 tahun, gejala yang paling sering ditemukan adalah demam (81,3%) dan batuk (71,9%), mayoritas pasien tidak memiliki komorbid. Terdapat hubungan yang signifikan antara NLR, ALC dan PLR dengan tingkat keparahan COVID-19 (p =0,007; p=0,002; p =0,013).Simpulan: NLR, ALC, dan PLR memiliki hubungan terhadap derajat keparahan COVID-19.